PENYULUHAN EDUKASI VAKSIN TERHADAP PEMBERITAAN HOAX DI MASYARAKAT DESA SANTAN SARI KECAMATAN SEMBAWA KABUPATEN BANYUASIN - Sulistijanto, Andi Budi (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2021)
The Covid-19 virus spread very quickly because many people did not comply with the health protocols implemented by the government. In the midst of the Covid-19 Pandemic, there were lots of Hoax reports that occurred which made people nervous because it would have an impact on government programs to suppress the development of the Covid-19 virus. The purpose of this counseling is to educate the community in Santan Sari Village, Sembawa District, Banyuasin Regency. This counseling educates the public about hoax reporting regarding the effects of vaccines. Because many people are afraid of getting vaccinated after seeing or reading news about the impact after being vaccinated. This counseling involved as many as 72 heads of families in Santan Sari Village. by looking at using effective communication the hoax news can be understood by local residents and raises speculation among the public. Education about the use of social media so that you don't easily believe the news you get from the internet. Overall, the use of social media is carried out by teenagers and mothers who hold community gatherings. By reporting on the effects of the Covid-19 vaccine, the community can help the government reduce the spread of the Covid-19 virus in Santan Sari Village. This counseling is aimed straight at social welfare. The more obedient the government regulations and health protocols, the better social welfare because residents can still carry out economic activities to meet household needs after being vaccinated